2019
DOI: 10.1111/jhn.12649
|View full text |Cite
|
Sign up to set email alerts
|

Deterioration of nutritional status of patients with locally advanced cervical cancer during treatment with concomitant chemoradiotherapy

Abstract: Background In Mexico, 80% women with cervical cancer are diagnosed at locally advanced stages and are treated with concomitant chemoradiotherapy. The treatment modality and catabolic state confer a nutritional risk. The present study aimed to thoroughly evaluate the nutritional status and change in body composition of locally advanced cervical cancer (LACC) patients throughout treatment. Methods An observational prospective study, carried out at the Mexican National Cancer Institute, included 55 LACC patients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 44 publications
(96 reference statements)
0
22
0
2
Order By: Relevance
“…In addition, we also found that the changes in body composition were different between SCC and adenocarcinoma; it implied that the protein synthesis rate may differ between SCC and adenocarcinoma, and may affect whole-body protein metabolism in humans [28]. The nutritional status may also deteriorate during CCRT and affect the clinical outcome in LACC patients [13]. Although we found that muscle loss after CCRT was a predictor of distant failures, our hypothesis and findings should be validated in future studies.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…In addition, we also found that the changes in body composition were different between SCC and adenocarcinoma; it implied that the protein synthesis rate may differ between SCC and adenocarcinoma, and may affect whole-body protein metabolism in humans [28]. The nutritional status may also deteriorate during CCRT and affect the clinical outcome in LACC patients [13]. Although we found that muscle loss after CCRT was a predictor of distant failures, our hypothesis and findings should be validated in future studies.…”
Section: Discussionmentioning
confidence: 60%
“…There were some limitations of our study. First, the retrospective nature of this study limits the longitudinal assessment of nutritional status, muscle strength, physical performance (e.g., gait speed), or systemic inflammatory markers (e.g., modified Glasgow prognostic score) during the course of CCRT [13]. Second, this study could not infer causality between the body composition parameters and distant failures.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…One study found that a third of patients with cervical cancer met diagnostic criteria for sarcopenia criteria despite not being clinically malnourished. Following treatment, 69% of patients were clinically malnourished and 58% were sarcopenic [65]. This was attributed to decreased calorie intake and early satiety.…”
Section: Sarcopenia In Pelvic Cancer Patientsmentioning
confidence: 99%
“…Depending on the instrument used, undernourishment is estimated to range between 0% and 42.8% at diagnosis, and to increase up to 69% by the end of treatment with concomitant chemoradiation therapy and followed by brachytherapy. Overweight and obesity are more common, since they occur in 61.8-75.8% of patients and, simultaneously, sarcopenia is present in 10.5%-33.3% 45,46 . Furthermore, around 40.8% of women with CC have some comorbidity 45 , which represents a huge challenge for diagnosis and nutritional approach, since a combination of the previous diagnoses can be found in a single individual 45 .…”
Section: Role Of Nutritional Status and Its Impact On Treatment Responsementioning
confidence: 99%